Dental Aerosol Hazard Prevention with Pre-procedural Antiseptic Mouthwashes (Comparative Study) - Wasnaa M Hameed; Nada J Radhi (College of Dentistry/ University of Baghdad, 2022)
Background: One of the recommended methods for reducing aerosol contamination during the daily regular usage of high-speed turbine and ultrasonic scaling is the use of preprocedural mouth rinse. Several agents have been investigated as a preprocedural mouth rinse. Chlorhexidine significantly reduce the viable microbial content of aerosol when used as a preprocedural rinse. Studies have shown that cetylpridinum chloride (CPC) mouthwash is equally effective as chlorhexidine in reducing plaque and gingivitis. This study compared the effect of 0.07% CPC to 0.2% chlorhexidine gluconate (CHX) as preprocedural mouth rinses in reducing the aerosol contamination by high-speed turbine. Materials and Methods: 36 patients were divided into three groups based on the preprocedural rinse used (0.2% CHX, 0.07% CPC and distilled water). Conservative treatment was done for 20 min. (10 min before rinsing and 10 min after rinsing) in the same closed operatory for all the patients after keeping blood agar plates opened at three standardized locations (patient chest, dentist chest and at 12-inch from patient mouth). Colony forming units (CFUs) on blood agar plates were counted, after incubation at 37°C for 48 hr. Statistical analysis was done with (SPSS version 21(. Results: This study showed that the two antiseptic mouthwashes significantly reduced the bacterial colony forming units (CFUs) in aerosol samples at three plates locations. Chlorhexidine rinses were found to be superior to cetylpridinum chloride when used pre-procedurally in reducing aerolized bacteria. The number of CFUs were higher at the patient's chest location as compared to other locations. Conclusion: 0.07% CPC and 0.2% CHX were effective as a pre-procedural rinse in reducing CFU count during dental treatment using high-speed turbine.